MENINGKATKAN RASA MENGUCAP SYUKUR MELALUI PEMBINAAN PEMAHAMAN BERKAT - Feri Aman Mendrofa; Riko Budiman; Riski Dermawan Tambunan; Kaleb Saputra Malau (JURNAL BEATITUDES, 2024)
Gratitude is acceptance of one's condition in any condition. This attitude is crucial for Christians to have as a form of respect for God's sovereignty. However, the importance of this attitude is often not found in Christians, especially when experiencing difficult times. One of the reasons is the belief that the blessings given by God are only material things in the form of wealth. This view then influences the gratitude of people who receive God's blessings. To anticipate the formation of this thought pattern, guidance is needed in understanding God's blessings as a whole. This coaching activity is intended to answer this problem. Using research results that have been published regarding God's blessing in Deuteronomy 28:1-14, the implementers carry out coaching using the lecture method. The coaching targets two mutual aid communities in Batam City, OMEFA and Family Batam. The participants were given coaching in four stages to provide a complete understanding of God's various blessings, which are very broad. This coaching is expected to make participants aware of God's blessings apart from material wealth.